Outpatient versus Inpatient Parotidectomy: A Systematic Review and Meta-analysis. (June 2020) - Forner, David; Lee, Daniel J.; Walsh, Chris; Witterick, Ian J.; Taylor, S. Mark; Freeman, Jeremy
Objective: Parotidectomies are commonly performed procedures by head and neck surgeons. Although parotidectomies are historically inpatient procedures, recent observational evidence has highlighted the potential for parotidectomies to be performed on an outpatient basis. This systematic review and meta-analysis sought to compare complications and unplanned health care utilization between patients undergoing outpatient versus inpatient parotidectomy. Data Sources: A systematic review was performed using MEDLINE, EMBASE, and the Cochrane Library. Review Methods: Studies comparing the outcomes of outpatient parotidectomy with those of inpatient parotidectomy were included. Risk of bias was assessed using the Newcastle-Ottawa Scale. Postoperative complications (hematoma, facial nerve dysfunction, seroma, fistulisation, Frey syndrome, and wound infection) and rates of 30-day readmission, reintervention, and emergency department presentation were compared. Results: We screened 1018 nonduplicate articles to include 5 studies, all of which were retrospective cohort studies. There were fewer complications found in the outpatient group (relative risk = 0.61, 95% confidence interval: 0.40-0.93). Outpatient procedures were more commonly performed on patients who lived close to the hospital, had fewer comorbidities, and had less extensive planned surgery. Conclusion: Outpatient parotidectomy appears safe in select patients with outcomes comparable with inpatient surgery. However, evidence overall is of low quality, and further work is needed to delineate a satisfactory set of criteria for appropriate patient identification.